Training for the Making of Singkong Leaves and Lele Fish for Communities in the Region of New Benda Kelurahan Pamulang-Tangerang Selatan - Sachriani; Yati Setiati Muhaenah (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
To increase community empowerment in the Benda Baru sub-district, Pamulang sub-district, South Tangerang City, in the form of product diversification of cassava leaves and catfish so that community welfare is created through optimizing the potential of cassava, processing various processed products of mashed beef jerky from cassava leaves and catfish that are varied, of high quality, nutritious and has a high selling value. This Community Service Program is aimed at the community as many as 16 mothers. The goal is to enable the community to plan and manage the potential of cassava to form/develop a group of people who are economically independent and prosperous. Outputs: (1) Products of cassava leaf jerky and catfish jerky (2) Publication of the activity of making pulverized cassava leaves and catfish jerky on YouTube. The method used in this activity is the provision of material, direct practice, and assistance. The presentation of the material was carried out in the local hall, with material on diversification of local food ingredients to introduce various alternative food sources and to introduce several examples of diversification of food based on existing local ingredients. The technique of making cassava leaves and catfish jerky is mentoring as well as the practice of making ground beef jerky and catfish jerky.